ENHANCING ACID STIMULATION TREATMENTS IN THE PETROLEUM FIELDS - Bedaiwi Abidin Alamri, Alamri, Mona Abdullah Aldawsari, Adel Saeed Alwadai, Saud Nasser Salem Al-Otaibi, Saad Saud Alrashoud, Batool Saad Barki Almsaudi, Khaled Alhamaidi Alanazi, Afaf Obaid Albalawi, Mofareh Abdullah, Mohammad AlDawsari, ,; Zainab Radhi A Almahdud, Khalid Majed Almutairi, Mohammed Murdi Abdullah Alqahtani, Shaykhah Saud Aloyayd, Mohsen Mohammed Alharbi, Turky hamed Zael Alenazy, (Chelonian Research Foundation, 2022)
This literature study specifically examines methods to enhance acidizing treatment in the oil fields, which are situated in the Western Desert. Acidizing is a chemical process that stimulates the permeability of rock formations around wellbores, hence increasing the flow of oil. The article presents a comprehensive examination of the matrix acidizing and acid fracturing techniques that are often used in carbonate and sandstone formations. The text underscores the need of choosing suitable acid concentrations and assessing reservoir conditions to enhance treatment results and avert unfavorable repercussions. The research emphasizes the important function of hydrochloric acid (HCl) in increasing oil production and examines the use of acid combinations, such as HCl and hydrofluoric acid (HF), for particular purposes. The analysis focuses extensively on the impact of formation damage and the skin effect on the effectiveness of acid therapy. The text discusses many methodologies for detecting and evaluating formation damage, including as well performance analysis, well logging, and core analysis. The research also examines techniques for enhancing acidizing therapy when faced with formation damage and the skin impact. The mentioned aspects include pre-treatment assessment, design of acid systems, implementation of diversion techniques to improve acid distribution, and the integration of acidic additives and enhancers. The significance of doing a post-treatment review to assess the effectiveness of the therapy and ascertain the need for further corrective actions is highlighted. Keywords: acidizing therapy, matrix acidizing, acid fracturing, formation damage, skin reaction.